Determining Seed Viability During Fruit Maturation to Improve Seed Production and Availability of New Citrus Rootstocks - de Carvalho, Deived Uilian; Boakye, Daniel A.; Gast, Tim; Leite Junior, Rui Pereira; Alferez, Fernando (Frontiers in Plant Science, 2021)
In recent years, the pressure for replanting and resetting huanglongbing (HLB or citrus greening) affected citrus groves has led to an inadequate seed supply for the most popular rootstock cultivars in the State of Florida, United States. Early fruit harvesting of citrus rootstock source trees might reduce fruit losses and enhance seed availability, especially in HLB-endemic and hurricane susceptible areas, if the physiological quality of the seeds is adequate. The effects of fruit maturity on seed quality and seedling performance of US-802, US-897, and US-942 citrus rootstocks were investigated for two consecutive growing seasons. The study included the evaluation of seed germination and nursery performance of the citrus rootstock seedlings. The germination test was performed in vitro, where seeds were hand-peeled, surface-sterilized and placed in culture tubes containing basal Murashige and Skoog medium. For the emergence test, seeds were sown in seedling trays containing sterilized growing substrate in a greenhouse with controlled-environment conditions. Rootstock fruits from all three varieties harvested in August and September had seeds with higher germination potential, as more than 90% of the seeds generated seedlings. US-942 had more % of emergence than US-802 and US-897, resulting in faster seed germination; in contrast, US-802 had the faster shoot growth rate. Assays on fruit abscission response showed that by August, fruit from all three varieties were responsive to ethylene and abscised, although response varied and was higher in US-942, suggesting the seeds were mature enough. Taken together, our findings indicate that fruits these three rootstocks can be harvested as early as August in contrast to the current procedures without losing germination potential. This will result in an increase in available seeds for nurseries in Florida.